Rencana Rute dan Moda Transportasi Cable Car Menuju Makassar World Class City - Megawati Viska H Maramis; Muh Yamin Jinca; Yashinta Kumala Dewi Sutopo (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2019)
Cable car transportation system has been popular in developed countries over the world as one of the tourist, business, and even has been developed as one of the public transportation system. This study aims to identify the ideal cable car transportation system implemented in cities over the world, analyze the potential application of this system in the city of Makassar specifically for tourism development, and conceptualize the planning of cable car routes and modes in the city of Makassar. The analytical methods used include, population rate of growth analysis, comparative study, spatial analysis, analysis of potential tourism, economic, social and environmental analysis. The results of the analysis show that there is a large potential application of cable car transportation system in the City of Makassar, especially in the Central City Region with a significant tourism market. Furthermore, the concept of planning is carried out on two components of transportation, that are routes and modes. The cable car transpostation route is then presented in the form of a cable car route map that serves the downtown area and is divided into three alternatives routes. Conceptually, the selection of a cable car route through popular tourist objects aims to present direct service connections between these tourist objects and present an urban views from the air which are, nature view or the beauty of building achitecture. Furthermore, the selected cable car transportation mode for Makassar is a detachable gondola specifically a monocable detachable gondola type due to its service characteristics that suitable with the condition of the City of Makassar and it is the most popular type of urban gondola used in urban areas.